Increase of competitiveness of the personnel: Internal control and stimulation (Путеводитель предпринимателя)
In work it is investigated and the assumption is put forward that one of tools of management of competitiveness of the personnel of workers is formation and development of system of internal control of the commercial organization, taking into account its close combination with a control system of the personnel. In such combined system there is a possibility to optimize a manpower, to state an estimation of competitiveness of the personnel, to enter the additional motivational and stimulatingfactors, allowing to raise competitiveness of the worker that, finally, will lead to growth of competitiveness of the organization and its production.